Evidence supporting the safety of pegylated diethylaminoethyl-chitosan polymer as a nanovector for gene therapy applications - Rondon, Elsa Patricia (2020)
Purpose: Diethylaminoethyl-chitosan (DEAE-CH) is a derivative with excellent potential as a delivery vector for gene therapy applications. The aim of this study is to evaluate its toxicological profile for potential future clinical applications. Methods: An endotoxin-free chitosan (CH) modified with DEAE, folic acid (FA) and poly-ethylene glycol (PEG) was used to complex small interfering RNA (siRNA) and form nanopar-ticles (DEAE12-CH-PEG-FA2/siRNA). Based on the guidelines from the International Organization for Standardization (ISO), the American Society for Testing and Materials (ASTM), and the Nanotechnology Characterization Laboratory (NCL), we evaluated the effects of the interaction between these nanoparticles and blood components. In vitro screening assays such as hemolysis, hemagglutination, complement activation, platelet aggregation, coagulation times, cytokine production, and reactive species, such as nitric oxide (NO) and reactive oxygen species (ROS), were performed on erythrocytes, plasma, platelets, peripheral blood mononuclear cells (PBMC) and Raw 264.7 macrophages. Moreover, MTS and LDH assays on Raw 264.7 macrophages, PBMC and MG-63 cells were performed. Results: Our results show that a targeted theoretical plasma concentration (TPC) of DEAE12-CH-PEG-FA2/siRNA nanoparticles falls within the guidelines’ thresholds: <1% hemolysis, 2.9% platelet aggregation, no complement activation, and no effect on coagulation times. ROS and NO production levels were comparable to controls. Cytokine secretion (TNF-α, IL-6, IL-4, and IL-10) was not affected by nanoparticles except for IL-1β and IL-8. Nanoparticles showed a slight agglutination. Cell viability was >70% for TPC in all cell types, although LDH levels were statistically significant in Raw 264.7 macrophages and PBMC after 24 and 48 h of incubation. Conclusion: These DEAE12-CH-PEG-FA2/siRNA nanoparticles fulfill the existing ISO, ASTM and NCL guidelines’ threshold criteria, and their low toxicity and blood biocompat-ibility warrant further investigation for potential clinical applications.